Green properties of dry-pressed alumina using a new synthesized copolymer able to act simultaneously as dispersant and binder with plastic character. Issue 14 (15th July 2021) - Hajri, Imen; Ben Romdhane, Mohamed Ramzi; Tessier-Doyen, Nicolas; Chartier, Thierry; Srasra, Ezzedine
Abstract: Statistical copolymers containing both carboxylate and hydroxyl functions have been synthesized in order to promote the dispersion of alumina suspensions in addition to the binding of pressed green disc-shaped specimens. In aqueous suspensions, the carboxylate groups are responsible for maintaining a high adsorption of the copolymer onto the alumina surface particles, thus increasing surface charges promoting a high electrostatic stabilization. The hydroxyl functions, which are not preferentially adsorbed on the surface i) participate in the steric stability of the suspension and, ii) confer a high mechanical resistance to green powder compacts compared to specimens classically shaped with 3 wt% of commercial polyvinyl alcohol and 1 wt% polyethylene glycol. Indeed, tensile stress to rupture evaluated by diametral compression is always greater than 3.5 MPa. The transition temperature of synthesized copolymers ranges from -10 to 57 °C, makes it possible to confer a plastic character to the organic system and to reach a high relative green density (around 63%) after compaction under 190 MPa at room temperature. Moreover, the effect of various molecular weights (from 11000 to 47000) on properties of spray-dried granules and of pressed compacts has been studied. A narrow spray-dried granule size distribution of corresponds to an optimal content of added copolymer, which in turn results in an optimal density of compacted parts. Optimal density values of the compacted parts follow the same trend as the highest particle size distribution corresponding to the optimal added copolymer content. The optimal values of densities correspond to an added amount of 1, 1.5 and 2 wt% respectively of high, medium and low copolymer's molecular weight.